2019
DOI: 10.2217/imt-2018-0200
|View full text |Cite
|
Sign up to set email alerts
|

Cd73: An Emerging Checkpoint for Cancer Immunotherapy

Abstract: CD73 is a novel immune checkpoint associated with adenosine metabolism that promotes tumor progression by suppressing antitumor immune response and promoting angiogenesis. The inhibition of CD73, in combination with immune checkpoint blockade, targeted therapy or conventional therapy, improves antitumor effects in numerous preclinical mouse models of cancer. Emerging evidence suggests that the combination of anti-CD73 and immune checkpoint blockade has promising clinical activity in patients with advanced soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
92
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 156 publications
0
92
1
Order By: Relevance
“…Immune suppression based on alternative regulation of immune checkpoint proteins, which results in T‐cell exhaustion, contributes to cancer development and progression . Increasing findings have shown that several immune checkpoint proteins play a key role in negatively regulating T‐cell activation, including programmed cell death receptor‐1 (PD‐1), cytotoxic T lymphocyte‐associated molecule‐4 (CTLA‐4), T‐cell immunoglobulin mucin‐domain‐containing‐3 (Tim‐3), T‐cell lymphocyte activation gene‐3 (LAG‐3), and B and T lymphocyte attenuator (BTLA) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immune suppression based on alternative regulation of immune checkpoint proteins, which results in T‐cell exhaustion, contributes to cancer development and progression . Increasing findings have shown that several immune checkpoint proteins play a key role in negatively regulating T‐cell activation, including programmed cell death receptor‐1 (PD‐1), cytotoxic T lymphocyte‐associated molecule‐4 (CTLA‐4), T‐cell immunoglobulin mucin‐domain‐containing‐3 (Tim‐3), T‐cell lymphocyte activation gene‐3 (LAG‐3), and B and T lymphocyte attenuator (BTLA) .…”
Section: Introductionmentioning
confidence: 99%
“…Immune suppression based on alternative regulation of immune checkpoint proteins, which results in T-cell exhaustion, contributes to cancer development and progression. 1,2 Increasing findings have shown that several immune checkpoint proteins play a key role in negatively regulating T-cell activation, including programmed cell death receptor- is disrupting the tumor microenvironment and restoring T-cell immune function. 8,9 Similarly, PD-1 inhibitors have been used for refractory and relapse lymphoma in clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that extracellular adenosine accumulated in the TME was largely produced by CD39/CD73 (20). The CD73-expressing tumor cells negatively regulated antitumor T-cell response and also promoted T cell apoptosis (35). In many cancer types, silencing CD73 inhibited tumor cell proliferation, viability, cell-cycle progression, leading to increased cell apoptosis (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…PABPC1 can combine with adenylate-rich sequences in mRNA under the action of high a nity, which plays an important role in post-transcriptional regulation of genes and is also involved in many metabolic pathways of mRNA, including adenylate polymerization/adenylation, mRNA transport, mRNA translation, microRNA degradation related regulation [45]. NT5E is a ubiquitously expressed glycosylphatidylinositol-xed glycoprotein, which can convert extracellular adenosine 5'-monophosphate to adenosine, and promote tumor development by inhibiting the anti-tumor immune response and promoting angiogenesis [46,47].…”
Section: Discussionmentioning
confidence: 99%